Energy policy distractions to renewable programs: a comparative assessment - Diane Kraal; Raphael J. Heffron; Mohammad Hazrati; Halima Hussein; Alicia Phillips (Sustainable Earth Reviews)
Abstract This article reviews renewable energy programs and policies as a result of the resurgence in demand for fossil fuels. Australia and selected countries are considered through the lens of energy justice. The range of countries evidence a resurgence in demand for fossil fuels, such as coal and gas, in the wake of disruptive global events. For example, the war in Ukraine, Middle East conflicts and pandemics such as COVID, can be seen as major global disruptors of renewable energy policies and projects. While Australia’s renewable energy in contrast to non-renewable energy is the focus, a mix of selected countries are chosen as comparators. The selected countries capture how governments are navigating the fiscal/economic, political and environmental tensions between renewable and non-renewable energy sources, policies, programs and laws. The two research questions ask ‘What current and proposed policy and laws address the energy justice economic, environmental and political aspects of the climate-related transition plans to renewable energy?’ as well as ‘Can the mix of non-renewable and renewable energy resources be quantitively ranked against economic, political and environmental pressures?’ The first question adopts the method of desktop research, conducted to produce policy and legislation data that are linked together with the qualitative method of narrative. For instance, the Australian legislative focus will be taxation law. For the second question, a quantitative method using the ‘energy justice metric’ is adopted. In particular, the research builds and adapts the parameters of the energy justice metric for all comparator countries. The results are plotted on a ternary phase diagram. The highlights of this article include the raising of awareness of energy policy distractions to renewable programs as a result of the resurgence in demand for fossil fuels, such as coal and gas, in the wake of disruptive global events. The essence of the article points towards how energy justice principles can enable resilience in policy decisions despite these disruptor issues and countries can continue to move towards a just transition to a low carbon economy. Plain English summary There are major dilemmas facing countries today in the shift towards sustainable energy policies. Issues include funding for renewable energy programs and policies, alongside the resurgence in demand for fossil fuels, such as coal and gas, due to disruptive global events (such as military conflicts, COVID-19 and extreme weather). This research considers the energy market tensions for the supply of fossil fuels, and the impact on renewable energy policies and laws. Through qualitative and metric-based questions, the trajectory of Australia, a fossil fuel rich country, is evaluated, and then its progress is compared with a range of countries including France, Trinidad-Tobago, Guyana, French Guiana, Iran, Malaysia, Kenya and Uganda. Thus, energy policy success and failures are explored from across the world. Qualitative and quantitative analysis of data using the energy justice metric shows the progress of their just energy transitions. The findings indicate positive steps in the journey of a just transition to a low-carbon economy. The modelling supports the research outcomes on key dilemmas arising from energy resource policies in these selected countries. Achieving the 2015 Paris Agreement emission targets remains elusive, but a justice-framed energy policy transition is the first step for many of these fossil fuel intense nations.